1998
DOI: 10.1007/pl00010849
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Einlaufeffekten auf den Wärmeübergang bei laminarer oszillierender Rohrströmung

Abstract: A theoretical analysis was performed to evaluate the influence of developing flow on the heat transfer associated with laminar oscillating pipe flow. Simplified analytical approaches are briefly discussed before an investigation based on the numerical solution of the conservation equations for mass, momentum and energy is presented, assuming constant wall temperature and an incompressible viscous fluid. Focusing on operating conditions as found in heat exchangers of regenerative thermal machines, like Stifling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Analytical and numerical analysis for laminar pipe flow showed that the influence of pulsation on Nu is more pronounced in the entrance region of the pipe and small at the downstream end [9,18,21,22,25]. The same observation was made by Habib et al [20] in their experimental investigation.…”
Section: Introductionsupporting
confidence: 64%
“…Analytical and numerical analysis for laminar pipe flow showed that the influence of pulsation on Nu is more pronounced in the entrance region of the pipe and small at the downstream end [9,18,21,22,25]. The same observation was made by Habib et al [20] in their experimental investigation.…”
Section: Introductionsupporting
confidence: 64%
“…They obtained good results predicting laminar flow and fully turbulent regime, but they did not obtain adequate results for transition flow regime. The heat transfer of reciprocating laminar pipe flow has been studied numerically by different authors [12,23]. In the high Reynolds number range, Su et al [24] studied the enhancement of the heat transfer due to reciprocating flow using the Saffman's RANS turbulence model while Walther [25] considered a lo Reynolds number keε turbulence model.…”
Section: Introductionmentioning
confidence: 99%
“…(18) and (19) need to be decomposed to yield the real part explicitly. Significant effort has been undertaken to visualize the flow and thereby verify the solution using various experiments (Harris, Peev, and Wilkinson, 1969;Walther et al, 1998;Simon and Seume, 1988). In Simon and Seume, (1988) plots of velocity profiles for laminar, incompressible, fully developed, and oscillating flow for eight dimensionless frequencies have been provided.…”
Section: Velocity Profilementioning
confidence: 99%
“…In Simon and Seume, (1988) plots of velocity profiles for laminar, incompressible, fully developed, and oscillating flow for eight dimensionless frequencies have been provided. Fig 4 shows the variation of velocity profiles in laminar oscillating pipe flow with time during one cycle Walther et al, (1998).…”
Section: Velocity Profilementioning
confidence: 99%
See 1 more Smart Citation